Stacking sequence selection for defect-free forming of uni-directional ply laminates. (8th February 2019) - Johnson, K.J.; Butler, R.; Loukaides, E.G.; Scarth, C.; Rhead, A.T.
Abstract: In order to meet demands for increased production rates of laminated composite components, aerospace manufacturing is being forced towards highly automated production processes such as forming. However, such automated processes increase the likelihood of inducing defects that lead to manufacturing cost and time inefficiencies which must be avoided. This paper introduces a new compatibility index, based on comparison of minimum energy (resin dominated) modes of adjacent plies that identifies stacking sequences which minimise defect formation. The index is validated using an experimental process where seven laminates with different stacking sequences are formed onto a complex tool geometry using an industrial double diaphragm former. Experimental results confirm that sequences with a high compatibility index produce defect-free parts at elevated temperature. Specifically, sequences with 90° interface angles (high compatibility indices) promote the most formable solutions and continuous 45° interfaces that spiral (e.g. 45/0/-45/90) which have a low compatibility index, produce the most problematic forming conditions owing to a shear locking behaviour. Laminate stacking sequence is thus shown to be a significant contributor, alongside temperature and vacuum rate, to quality of formed parts. The compatibility index method can therefore be used to increase production rate and quality in laminated composite manufacturing, leading to significant cost and efficiency savings.